Unlocking Agrotourism Potential: Navigating Contemporary Development Communication Challenges in Tamanmartani Village - Murti, Desideria Murti Cempaka Wijaya; Yurkova, Darya (Fakultas Ilmu Komunikasi UKWMS, 2025)
The aim of this study is to understand the intricate relationship between development communication in village government level to develop agrotourism, village entreprise, and engage the community in the same time. There are two stages of this project. First, the study learned the statusquo of the village officials’ programs to develop agrotourism by examining the area’s customes, culinary traditions, and cultural heritage. Through learning the exisiting programs, this study can understand the communication tactics in promoting community engagement. Second, the study looked at the issues surround the development communication by exploring the obstacles that the stakeholders faced. Through qualitative methods, the study discovered the internal obstacles in the complex web of subdistrict government level. The results show three important process to improve agrotourism from establishment, identification, and development. Meanwhile there are wide range of challenges which restrict the agrotourism from infrastructural, capacity, stakeholder collaboration, and leadership. The findings of this research can be userful for scholars and practitioners in development communication especially in the landscape of agrotourism program in the village.. ABSTRAK Tujuan dari penelitian ini adalah untuk memahami kompleksitas hubungan dalam komunikasi pembangunan yang dihadapi oleh pemerintah kalurahan dalam mengelola agrowisata untuk mendukung usaha mereka dan meningkatkan keterlibatan masyarakat. Penelitian ini dilakukan melalui dua tahap penting. Pertama, penelitian meneliti langkah-langkah status quo yang telah diambil oleh pejabat desa untuk memanfaatkan agrowisata dengan melihat pada aspek adat, tradisi kuliner, dan warisan budaya daerah. Kedua, penelitian ini meneliti isu-isu kompleks yang hadir dalam bidang komunikasi pembangunan, khususnya terkait dengan menarik wisatawan ke desa agrowisata. Penelitian kami menggunakan metodologi kualitatif dapat menambah pemahaman yang lebih dalam tentang tantangan komunikasi dalam jaringan kompleksnya pemerintahan desa. Hasil penelitian menunjukkan tiga proses penting dalam meningkatkan usaha agrowisata yakni pendirian, identifikasi, dan pengembangan. Sementara itu, tantangan yang membatasi mulai dari infrastruktur, kapasitas, kolaborasi pemangku kepentingan, dan kepemimpinan. Temuan ini dapat bermanfaat bagi akademisi dan praktisi dalam menelaah komunikasi pembangunan khususnya dalam pengembangan lanskap agrowisata.